FUNGSI HUKUM PENYELENGGARAAN RUMAH SAKIT DAN PRAKTEK DOKTER - Indrati Rini (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2005)
The are 3 law subjects involved in the field of health care, including: medical doctor; patient and hospital. The relationship implementation among those parties has been set in specific regulations, so that in the end it will make a harmony in the community.